10 years of GWAS discovery: biology, function, and translation - Visscher, P; Wray, N; Zhang, Q; Sklar, P; McCarthy, M; Brown, M; Yang, J (Cell Press, 2017)
Application of the experimental design of genome-wide association studies (GWASs) is now 10 years old (young), and here we review the remarkable range of discoveries it has facilitated in population and complex-trait genetics, the biology of diseases, and translation toward new therapeutics. We predict the likely discoveries in the next 10 years, when GWASs will be based on millions of samples with array data imputed to a large fully sequenced reference panel and on hundreds of thousands of samples with whole-genome sequencing data.